La République romaine et le mercenariat au temps des Guerres Puniques - Anthony-Marc Sanz (Mélanges de la Casa de Velázquez, 2011)
Rome, victorious in the Punic Wars, whose army was organised on an essentially civic basis, was in contact with the great Western Mediterranean mercenary markets of the 3rd and 2nd centuries BC. Some historical episodes in the course of which the Romans employed mercenaries merit analysis in order to understand how they dealt with the experience of a type of military organisation so alien to their system, bearing in mind that in some cases involving the recruitment of Celtiberian mercenaries they were influenced by traditions that appear to hark back to the testimonies of their own contemporaries. Placed in the context of the lively debates prompted by the questions of war and conquest in Roman ruling circles, these accounts bring back to life the history of what was at once a rejection and an affirmation: faced with the mercenary armies of the great powers of the time, the Republic ostensibly rejected the idea of paid military service and stood up for the model of an armed citizenry, for reasons of both ideology and self-interest.